Nurses' experience in providing continuity of care for people with mental disorders after hospitalization in primary health care: A qualitative study - Putra, Rizki Widmah; Umar, Zahra Umaya Bin (Journal of Community Nursing and Primary Care, 2024)
Background: Continuity of care for individuals with mental disorders after hospitalization is essential to prevent relapse and support long-term recovery, particularly within primary health care settings. Nurses play a key role in ensuring continuity of care; however, they often encounter challenges related to workload, limited resources, inadequate mental health training, and systemic constraints. Objective: This study aimed to explore nurses’ experiences in providing continuity of care for patients with mental disorders following hospital discharge in primary health care settings. Methods: A qualitative descriptive study design was employed. Data were collected through semi-structured interviews with registered nurses working in primary health care facilities. Participants were selected using purposive sampling. The interview data were analyzed using thematic analysis to identify patterns and key themes related to nurses’ experiences in delivering continuity of care. Results: Four main themes emerged from the analysis: building therapeutic relationships, resource constraints and workload, professional development needs, and systemic barriers. Nurses emphasized the importance of trust, empathy, and ongoing communication in maintaining continuity of care. However, high workloads, limited human and material resources, insufficient specialized mental health training, and structural limitations within the health system were reported as major barriers that hindered consistent and comprehensive care delivery. Conclusion: Continuity of care for patients with mental disorders in primary health care settings remains challenged by individual, organizational, and systemic factors. Strengthening nurses’ capacity through targeted mental health training, improving staffing and resource allocation, and implementing supportive policies are crucial to enhance continuity of care and improve mental health outcomes.